2022
DOI: 10.12998/wjcc.v10.i25.8872
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine poisoning caused by improper mixing of household disinfectants during the COVID-19 pandemic: Case series

Abstract: BACKGROUND Misuse of disinfectants during the coronavirus disease 2019 pandemic has led to several poisoning incidents. However, there are few clinical case reports on poisoning caused by improper mixing of household disinfectants. AIM To summarize the clinical characteristics and treatment effects of chlorine poisoning caused by improper mixing of hypochlorite bleach with acidic cleaning agents. METHODS We retrospectively analyzed baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The results showed that the majority of survey respondents reported at least one adverse event associated with the use of disinfectants, ranging from skin irritation to poisoning, and significant differences in awareness and performance mean scores among various educational levels (p < 0.001) as well as the level of performance between males and females (p < 0.001) [4]. Additionally, studies from Italy and China showed toxicological events due to the mishandling of disinfectants [5,6]. These reports collectively suggest that there was some degree of a lack of understanding in the general public as to how household disinfectants work.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the majority of survey respondents reported at least one adverse event associated with the use of disinfectants, ranging from skin irritation to poisoning, and significant differences in awareness and performance mean scores among various educational levels (p < 0.001) as well as the level of performance between males and females (p < 0.001) [4]. Additionally, studies from Italy and China showed toxicological events due to the mishandling of disinfectants [5,6]. These reports collectively suggest that there was some degree of a lack of understanding in the general public as to how household disinfectants work.…”
Section: Introductionmentioning
confidence: 99%